Wicksell, secular stagnation and the negative natural rate of interest - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2016)
Knut Wicksell's concept of the natural (or neutral) rate of interest, introduced between the end of the 19th and beginning of the 20th centuries, has played an important role in modern monetary macroeconomics, especially after the development of inflation targeting policy in the 1990s. More recently, the revival of Alvin Hansen's 1939 secular stagnation hypothesis by Larry Summers and others has brought to the fore the notion of a negative natural rate of interest, in the sense that there is no positive rate of interest able to equilibrate saving and investment at full-employment income. The present paper investigates whether the negative natural rate of interest may be found in Wicksell. It also examines in what extent the idea of secular stagnation is compatible with his original theoretical framework.
Keywords: B13; B22; E32; E40; 330; Wicksell; secular stagnation; natural rate of interest; Hansen; population growth